Co oznacza "godność człowieka"? - Arno Anzenbacher (Jesuit University Ignatianum in Krakow, 2017)
The reflection upon human dignity taken up by the author was concentrated around three issues. The context of the first one is legal-ethical issues, with special emphasis put on the relations between understanding dignity and rights of a human being, both as an individual-person and as a citizen of a particular community. The second thread of deliberations was determined with a question about the essence of human dignity, with reference to biblical texts as well as the texts of modern philosophy (Kant, Hegel). The third aspect of dignity was framed by its understanding as a world view basis for contemporary human being. And this is subject to the pluralisation process which, according to the author, leads to erosion of essential understanding of this concept and risk of ceasing treating it as a basic and universal ethical norm protecting every human being.